#### Answer

$\color{blue}{-\dfrac{12}{5}}$

#### Work Step by Step

Simplify using the PEMDAS rule for order of operations.
The PEMDAS rule summarizes the order of operations:
First Priority; P - parentheses or grouping symbols
Second Priority: E - exponents
Third Priorirty: M/D - multiplication or division, whichever comes first from the left
Fourth Priority: A/S - addition or subtraction, whichever comes first from the left
Simplify within the parentheses/grouping symbols to obtain:
$=\dfrac{6(-4)-3^2(-2)^3}{-5(-2+6)}
\\\dfrac{6(-4)-3^2(-2)^3}{-5(4)}$
Apply the exponents:
$=\dfrac{6(-4)-9(-8)}{-5(4)}$
Perform the multiplications:
$=\dfrac{-24-(-72)}{-20}$
Perform the subtraction then simplify:
$=\dfrac{-24+72}{-20}
\\=\dfrac{48}{-20}
\\=\color{blue}{-\dfrac{12}{5}}$